Liquid Anaerobic Digestate as Sole Nutrient Source in Soilless Horticulture—Or Spiked With Mineral Nutrients for Improved Plant Growth - Weimers, Kristina; Bergstrand, Karl-Johan; Hultberg, Malin; Asp, Håkan (Frontiers in Plant Science, 2022)
Digestate from biogas production high in plant-available macro- and micronutrients could replace mineral fertilizer in protected (soilless) horticulture. Previous use of digestate has shown that low concentrations of plant-available phosphorus (P) and sulfur (S) may be limiting factors for growth when using digestate as the sole fertilizer. In this study, digestate collected from a municipal biogas plant in Sweden was nitrified in a moving-bed biofilm reactor prior to use as fertilizer. A greenhouse pot trial with pak choi grown in peat based growing medium was established to assess: i) macro- and micronutrient availability in the digestate, with particular focus on P and S; and ii) the effect of amending the digestate solution with nutrients considered to be lacking (P, S, magnesium (Mg), manganese (Mn), boron (B), and molybdenum (Mo)). The results showed that plants fertilized with raw digestate suffered from S and B deficiency and early P deficiency. Supplementing the digestate with nutrients origin from mineral salts resulted in sufficient plant tissue concentrations of all elements except S. Marketable yield was similar to that achieved using standard mineral fertilizer and dry matter yield was 17% higher. In the light of the present results the use of nitrified digestate in soilless plant production seems as a fruitful way forward to recycle organic nutrients from waste streams. In the case where a strict organic protocol is not needed, amendment with inorganic nutrients may be a way to increase the utilization of the organic derived nutrients.